Better Knowledge Need Not Affect Behavior : A Randomized Evaluation of the Demand for Lottery Tickets in Rural Thailand - Zenker, Juliane; Wagener, Andreas; Vollmer, Sebastian (Published by Oxford University Press on behalf of the World Bank, 2020)
Many households in developing countries spend substantial amounts on lottery tickets but have only poor knowledge about the properties of the game and hold upwardly biased beliefs on the prospects of winning. To test whether more accurate knowledge reduces lottery participation, households in rural Thailand were informed, in a randomized intervention, on the actual probability distribution of the Thai Government Lottery. This indeed led to a better knowledge about the Thai Government Lottery in the treatment group. However, the improved knowledge did not (substantially) affect the willingness to pay for lottery tickets.